Analisis Nilai dalam Kakawin Aji Palayon - A.A. Made Pujiari (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2021)
Kakawin is one of the literatures used in Yadnya ceremonies in Bali in particular. In the yadnya ceremony, the activity of developing kakawin accompanies the ceremony in a melodious and meaningful way. Kakawin is also commonly referred to by other terms, namely wirama, tembang gede and sekar agung. One of the kakawin who plays an important role in increasing the belief and trust of the Balinese people in the existence of the afterlife is Kakawin Aji Palayon. Kakawin Aji Palayon tells of the journey of the atma (spirit) from dying (coming out of the body) to Sang Hyang Widhi in Heaven. Kakawin or literary work has values related to all things that are good. Likewise in Kakawin Aji Palayon, it contains good values of life that encourage people to be positive in their own lives or in society.